An Analysis of Eating Disorders in Adolescent Idiopathic Scoliosis: A Prospective Cross-sectional Study in a Female Population. Issue 7 (1st April 2021) - Cantele, Francesca; Maghini, Irene; Tonellato, Michele; Meneguzzo, Paolo; Favaro, Angela; Masiero, Stefano
Abstract : Study Design: Prospective cross-sectional study. Objective: We designed this study to investigate whether adolescent girls with idiopathic scoliosis show a predisposition for eating disorders (EDs) and alterations of the quality of life and body image self-perception, compared to same-age healthy females. Summary of Background Data: Idiopathic scoliosis is the most common spinal deformity of adolescence. Recent findings about the impairment of the self-body image in adolescents with idiopathic scoliosis provide a common trait of scoliosis and EDs and could lead to the suspicion of an association between these two pathological conditions. Despite this, current literature shows the lack of evident results about the impact of adolescent idiopathic scoliosis (AIS) on the possibility to develop of EDs. Methods: One hundred forty-four females with diagnosis of AIS (aged 10–18 years) formed the scoliosis group. One hundred forty-six same-age healthy girls were enrolled in the control group. For all subjects, we considered sport practice. Only for Scoliosis Group, we also considered the severity of scoliosis, the use of brace and the practice of physiotherapy scoliosis-specific exercises. The participants were asked to answer to the Scoliosis Research Society-22 revised Patient Questionnaire (SRS-22r) and the Eating Disorders Inventory (EDI). Results: In the scoliosis group, significantly lower scores on the SRS-22r total and in the self-image domain were detected. The two groups showed differences in the total EDI score and in the body dissatisfaction EDI's domain. Severity of scoliosis was correlated with worse SRS-22r total score and SRS-22r self-image domain score. There were no differences in the scores of the SRS-22r and EDI between braced and nonbraced subjects. Lower scores in SRS-22r total and self-image domain were found in girls who practiced physiotherapy exercises. Subjects who practiced a sport showed higher SRS-22r total scores. Conclusion: The AIS cohort in our study demonstrated lower levels of eating psychopathology than healthy controls. Surprisingly, eating behavior does not seem to be affected by orthotic management. However, quality of life and self-body image could be impaired in scoliotic girls, especially when they practice physiotherapy exercises, whereas those who practice sport seem to be preserved in this regard. Level of Evidence: 4 Abstract : According to the results obtained with two self-administered surveys, girls affected by adolescent idiopathic scoliosis show lower levels of eating psychopathology than healthy controls, but their quality of life and their self-image are impaired. Parents could be reassured about consequences of scoliosis treatment and scoliosis itself on adolescents' eating behavior.